Pain amplification—A perspective on the how, why, when, and where of central sensitization. Issue 2 (27th February 2018) - Woolf, Clifford J.
Abstract : Pain is an essential physiological defense against danger, be it external, from the environment, or internal, arising from within the body. The initiation of this acute defensive pain is driven by activation in the periphery of the terminals of high threshold nociceptor sensory neurons by intense or irritant noxious stimuli and comprises both the distinct unpleasant sensation of pain and protective motor responses. Clinical pain, is though, very different from the immediate detection of and reaction to noxious stimuli, it includes ongoing pain and development of pain hypersensitivity in the presence of tissue damage, after nerve injury and in some cases, in the absence of any peripheral pathology. In all these situations, a prominent feature and sometimes prime driver of the pain, is an altered modulation of pain processing within the central nervous system, an amplification consequent on increased excitability and/or reduced inhibition in specific neural networks, which constitute the phenomenon of central sensitization. Recognition of the importance of central sensitization for the maintenance and manifestation of clinical pain states has led to an appreciation that such pain typically is an expression of an altered/disease state of nociceptive circuits in the central nervous system, one triggered but not necessarily sustained by peripheral injury, rather than only a symptom of some ongoing peripheral pathology, and treatment needs to be targeted accordingly.